TURKIC BORROWINGS IN ENGLISH: A LINGUISTIC JOURNEY FROM THE STEPPES TO MODERN VOCABULARY - Khamdamov Ramzbek Madaminjonovich (Modern American Journals, 2025)
This article examines the contribution of Turkic languages to English through centuries of cultural, commercial, and military contact. From the Silk Road to the Ottoman Empire's influence on European diplomacy, Turkic words have enriched English vocabulary across food, clothing, military terminology, architecture, and commerce. Through etymological analysis, this study demonstrates that Turkic borrowings have become integral to English communication and reflect cross-cultural exchange patterns.
Keywords: Etymology, Loanwords, Turkic Languages, English Language History, Ottoman Empire, Linguistic Borrowing